New Vespertilio murinus (Chiroptera) Winter Records. An Indication of Expansion of the Species’ Winter Range? - Godlevska, L.V. (Вестник зоологии, 2013)
Absence of winter records, known long distance movements of parti-coloured bats ringed in North-eastern (NE) Europe, and some observations of seasonal concentrations of migrating animals had enabled to consider Vespertilio murinus, until quite recently, as a migratory species wintering outside Ukraine and NE Europe as a whole. During the last years the species had been found in the winter season (November — middle March) in Ukraine in 14 provinces and in the AR Crimea: contact records in 7 provinces, observations of autumn display song in 9 provinces and in the AR Crimea. Analysis of the data allows to assert that at present the whole territory of Ukraine belongs to the winter range of V. murinus. New winter records of V. murinus from Ukraine and other countries of NE Europe should probably be considered as an evidence of the expansion of the species’ winter range, that may be conditioned by the appearance of big massifs of rock-like structures (= multi-storey buildings) in plain regions.